Validity and reliability of the Turkish version of the central sensitization inventory - Ela Düzce Keleş; Murat Birtane; Galip Ekuklu; Cumhur Kılınçer; Okan Çalıyurt; Nurettin Taştekin; Enes Efe Is; Ayşegül Ketenci; Randy Neblett (Archives of Rheumatology, 2021)
Objectives: The aim of this study was to translate the Central Sensitization Inventory (CSI) into the Turkish language, to perform a psychometric validation, and to investigate its reliability in patients with chronic spinal pain with an organic origin, patients with fibromyalgia, and pain-free control individuals. Patients and methods: Between April 2016 and February 2017, the translation of the original English version of the CSI into Turkish was performed using the forward-backward translation method. A total of 100 fibromyalgia patients (6 males, 94 females; mean age: 45.0±8.4 years; range, 25 to 60 years), 100 patients with chronic spinal pain with an identified organic origin (CSPO), (10 males, 90 females; mean age: 43.8±9.7 years; range, 21 to 60 years), and 100 healthy controls (8 males, 92 females; mean age: 35.8±10.1 years; range, 25 to 55 years) were included in the study. Demographic characteristics were collected. Test-retest reliability was determined by re-administering the CSI-Turkish (CSI-Turk) two weeks after the first application. Results: The internal consistency (Cronbach’s alpha) was found to be 0.92 and the intraclass correlation coefficient was 0.93. Patients with fibromyalgia, a very common central sensitivity syndrome (CSS), had the highest mean CSI-Turk scores, and healthy controls had the lowest. Using the recommended cut-off score of 40 resulted in 87% sensitivity and 90% specificity in distinguishing between fibromyalgia and control individuals. Conclusion: This study suggests that the CSI-Turk can be effectively used as a screening tool to elucidate CS-related symptomology among patients with chronic pain with a high internal consistency, test-retest reliability, sensitivity, and specificity.